The Role of Affective Commitment to the Readiness for Changes of E-Puskesmas Entry Officers in Mojokerto District - Farida Wahyu Utami; Ratna Wardani (Journal for Quality in Public Health, 2021)
Every Puskesmas is obliged to organize a Puskesmas Information System. The Puskesmas Information System can be held electronically and / or non-electronically. E-puskesmas is an application developed to fulfill the need for digital data recording at puskesmas. This study aims to analyze the factors of communication and transformational leadership that directly affect and are mediated by the affective commitment factor to readiness. Data collection was conducted through a survey of 172 E-Puskesmas entry officers at 27 Puskesmas in Mojokerto Regency. Statistical test using path analysis. The sampling technique is multistage sampling technique. Statistical results show a positive effect of transformational leadership on affective commitment with a sig value of 0.02 and readiness to change with a sig value of 0.011. Communication has a positive effect on affective commitment with a sig value of 0.00 and readiness to change with a sig value of 0.00. Affective commitment has a positive effect on readiness to change dengan nilai sig 0.00. The limitation in this research is the method of collecting questionnaires with google form so that it allows different perceptions by respondents.